(untitled) (The Journal of Psychology and Sociology, 2015)
In this article is researched connection between human voice build ing system and emergence of psychological clenches while his social adaptation. Base for definition of such interdependence gives the reducing of voice sounding and timbre degradation of child’s voice because of reducing emotional expressions required by parents, educators in the kindergartens, teachers ets. It is also considered the question of removal of neurotic conditions effects by means of special voice adjusting. The author, basing on his rich multyyears long training practice, finds out the main parameters of voice adjusting. Three items of sound, which make its base Breathing, Frequency characteristic of timbre and Emotional filling adjusted by definite way, let the person conducting own voice, though the person has no natural abilities to sing. For this purpose is used the focusing of attention on two organsThroat and Diaphragm which are responsible for sound making. But the main method which leads to natural sounding is the muscle relaxation. The main principal definating the exact adjusting of voice is the lack of density of its sounding. Gradual work at special organization of breathing and conducting of overtones characteristics of voice colour by means of regulations of diaphragm and throat functions gives possibility to use the voice of each person as an instrument for removal of many psychological clenches. Person’s voice can serve as a reliable indicator of his psychic condition and as an instrument of his harmonization.